Biomechanical properties and corrosion resistance of plasma-sprayed Fish Scale Hydroxyapatite (FsHA) and FsHA-Doped Yttria-Stabilized Zirconia Coatings on Ti6Al4V alloy for biomedical applications - Ismail Zainol (Tanjung Malim, 2023)
Biomechanical properties and corrosion resistance of plasma-sprayed Fish Scale Hydroxyapatite (FsHA) and FsHA-Doped Yttria-Stabilized Zirconia Coatings on Ti6Al4V alloy for biomedical applications by Ismail Zainol